2017
DOI: 10.7759/cureus.1006
|View full text |Cite
|
Sign up to set email alerts
|

Human Listeriosis Presenting as Breast Abscess: Report of a Rare Case

Abstract: An abscess is defined as a collection of pus in various tissues of the body including skin and other organs. Abscesses most commonly are formed on the skin under the armpits, groin areas, and rectal areas. Most abscesses involve microbial infections with few remaining sterile. The treatment of abscesses includes both medical and surgical intervention. In the era of multidrug resistance, isolation and identification of the causative microbe and testing for antimicrobial susceptible patterns assume greater signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…and 11 F-fluorodeoxyglucose-positron emission tomography-computed tomography confirmed endocarditis. 12 Although…”
Section: Monocytogenesmentioning
confidence: 84%
See 3 more Smart Citations
“…and 11 F-fluorodeoxyglucose-positron emission tomography-computed tomography confirmed endocarditis. 12 Although…”
Section: Monocytogenesmentioning
confidence: 84%
“…As all these pathogenic organisms are usually food‐borne, the study concluded that post‐transplant food‐borne ailment was a critical cause of morbidity and mortality in such patients. A potential Listeria ‐induced endocarditis case was reported in a 74‐year‐old hemodialysis patient with bacteraemic L. monocytogenes , and 11 F‐fluorodeoxyglucose‐positron emission tomography‐computed tomography confirmed endocarditis 12 . Although Listeria is not a usual causative agent of infective endocarditis, the high‐risk immunosuppressed and the elderly are susceptible 13 .…”
Section: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Listeria is a bacterium that generally affects humans in the form of food poisoning and neonatal meningitis. Such an organism was reported to cause breast abscesses [ 19 ].…”
Section: Reviewmentioning
confidence: 99%